Pocket Tutor Understanding ABGs & Lung Function Tests - Thillai, M. Muhunthan (Pocket Tutor, 2020)
This book focuses on the understanding ABGs & lung function tests second edition. Lung function and arterial blood gas tests are fundamental to many areas of medicine. This book describes key respiratory terminology and then provides a step-by-step guide to understanding the tests, defining abnormal results and interpreting key abnormalities. This background information (Chapters 1-3) is then used to explain common systemic ABG and lung function abnormalities (Chapters 4-8). The second edition of the book extensively revised the introductory chapters on the core science that underpins lung function testing and the analysis of ABGs. In doing so, this book clearly explain these principles to a new generation of medical students, junior doctors, nurses, physiotherapists and health professionals who evaluate patients with lung disease. This book also expanded the chapters on asthma and COPD to reflect the latest management guidelines, and to show how lung function testing and ABG analysis remain of vital importance in the management of lung disease. This book also included as many real-life clinical scenarios as possible which will further guide the interpretation of ABG and lung function results in your own daily clinical practice.